Cover Picture: Physicochemical and Electronic Properties of Cationic [6]Helicenes: from Chemical and Electrochemical Stabilities to Far‐Red (Polarized) Luminescence (Chem. Eur. J. 51/2016). Issue 51 (25th November 2016) - Bosson, Johann; Labrador, Geraldine M.; Pascal, Simon; Miannay, François‐Alexandre; Yushchenko, Oleksandr; Li, Haidong; Bouffier, Laurent; Sojic, Neso; Tovar, Roberto C.; Muller, Gilles; Jacquemin, Denis; Laurent, Adèle D.; et al.
Abstract : A chiral cationic [6]helicene, which is depicted in the image, has been found to be a powerful dye and fluorophore that emits circularly polarized light in the red to far‐red region. More information can be found in the Full Paper by E. Vauthey, J. Lacour et al. onpage 18394 ff.